THE PROVISION OF LEMONGRASS OIL (Cimbopogon cirates) WITH DIFFERENT CONCENTRATIONS AS AN ANESTHETIC MATERIAL AGAINST THE SURVIVAL RATE OF BLACK GHOST FISH (Apteronotus albifrons) WITHIN 12 HOURS - Dina Widya Ningrum; Hariyadi Hariyadi; Sri Samsundari (Universitas Muhammadiyah Malang, 2024)
Transportation and handling processes in ornamental fish culture often cause stress that can reduce fish survival and quality. One method to minimize stress during handling and transportation is the application of anesthetic agents. Natural anesthetics are increasingly preferred because they are environmentally friendly and safer than synthetic chemicals. Lemongrass oil contains bioactive compounds with sedative properties and has potential as a natural anesthetic for ornamental fish. Therefore, this study aimed to evaluate the effect of lemongrass oil on anesthesia induction time, recovery time, and survival rate of black ghost fish. The study employed an experimental method using a Completely Randomized Design (CRD) consisting of five treatments and three replications. The treatments included different concentrations of lemongrass oil: 1 mL/L, 1.5 mL/L, 2 mL/L, 2.5 mL/L, and 3 mL/L, while the control treatment was conducted without anesthetic addition. Observed parameters included induction time, recovery time, survival rate, and water quality parameters such as temperature, dissolved oxygen (DO), and pH. The results showed that lemongrass oil significantly affected the anesthetic response and survival rate of black ghost fish. The fastest induction time was obtained at 3 mL/L with an average of 3.34 minutes, while the fastest recovery time was observed at 1 mL/L with an average of 5.34 minutes. The highest survival rate (80%) was achieved at 1 mL/L, whereas the lowest survival rate (20%) occurred at 3 mL/L. Water quality remained within suitable ranges during the study. These findings indicate that lemongrass oil at 1 mL/L is the most effective concentration as a natural anesthetic for black ghost fish.